DESIGN OF THE PRODUCTION PROGRAM AND AUDIT OF THE CONSTRUCTION OF A RESTAURANT ESTABLISHMENT - KRYVORUCHKO, MYROSLAV; ANTONENKO, АRTEM; RATUSHENKO, ANTONINA; GORKUN, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is dedicated to step-by-step modeling of the production program of a public catering enterprise consisting of two structural units – a Georgian restaurant seating 90 people and a pizzeria seating 30 people. For the studied enterprise, based on averaged recommended project payback indicators, cyclicity of one seat in dining halls of its subdivisions has been defined. In accordance with generally accepted food consumption rates at public catering enterprises of a certain type, a daily design menu of the designed facility has been formed, which, in addition to a serving size of dishes (products, drinks), also includes group-by-group daily sales volume of the corresponding items. The following items were identified for analysis: in the restaurant – signature dishes, cold appetizers, first dishes, main dishes, garnishes, sweet dishes, cold drinks, alcoholic beverages in assortment; in a pizzeria – cold appetizers, first dishes, pizza in assortment, sweet dishes, cold drinks, beer. The emphasis has been made on a minimalist approach to menu formation, namely reducing the range of dishes, which gives the enterprise a number of advantages. At the same time, the kitchen can focus on food quality and freshness control by simplifying recipes and improving visual presentation of dishes. An approximate calculation of daily raw material reserves of the enterprise and their structurization according to certain indicators (origin, possibility of commodity neighborhood, temperature storage regime) have been carried out. In accordance with forecasted volume, the process of warehousing and storage of foods has been designed. For this purpose, functional zones and their approximate areas (non-refrigerated storerooms, cold chambers, charging area with a loading ramp) have been defined, and operations for moving raw materials and goods between the enterprise’s divisions have been structured. Also, equipment has been selected by type, number and brand to complete functional areas and arrange proper warehouse functioning.
Keywords: public catering enterprise; production program; cyclicity of a seat; food consumption rate; daily design menu; construction; warehousing and storage of foods